2015
DOI: 10.1093/abbs/gmv037
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of bone morphogenetic protein 5 in human lung squamous cell carcinoma and adenocarcinoma

Abstract: Bone morphogenetic proteins (BMPs) play important roles in tumor cell proliferation, metastasis, and invasion. However, the expression patterns of BMPs in patients with non-small-cell lung cancer (NSCLC) and their correlations with NSCLC pathogenesis have not been examined yet. In this study, the mRNA levels of BMP family members in NSCLC tissues were analyzed and results showed that the mRNA levels of BMP5 and BMP7 were significantly down-regulated and up-regulated, respectively, in tumor tissues compared wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 31 publications
2
17
0
Order By: Relevance
“…The phosphorylated Smad1/5/8 together with Smad4 translocated into nucleus and control cycle progression [37]. It has been reported that the mRNA levels of BMP5 was significantly decreased in NSCLC tissues [38]. In this study, the changes of downstream protein BMP5 correlated with PinX1-stimulated cell proliferation.…”
Section: Discussionmentioning
confidence: 55%
“…The phosphorylated Smad1/5/8 together with Smad4 translocated into nucleus and control cycle progression [37]. It has been reported that the mRNA levels of BMP5 was significantly decreased in NSCLC tissues [38]. In this study, the changes of downstream protein BMP5 correlated with PinX1-stimulated cell proliferation.…”
Section: Discussionmentioning
confidence: 55%
“…From this, a prognostic prediction model was constructed, the RiskScore of patients was calculated, and prediction and verification were also carried out. Among all 14 prognosis-specific immunerelated genes, 9 (e.g., PSMD11, PPIA, MIF, BMP5, DKK1, PDGFB, ANGPTL4, IL1R2, and THRB) (26)(27)(28)(29)(30)(31)(32)(33)(34) have been reported to be involved in the immune microenvironmentassociated pathogenesis of lung adenocarcinoma or suggested to be significant predictors of recurrence-free or overall survival. This implies that our bioinformatics analysis using TCGA and ImmPort cohorts has prognostic value.…”
Section: Discussionmentioning
confidence: 99%
“…Zhao et al (22) demonstrated that CTDSPL2, as a Smad phosphatase, plays a critical role in bone morphogenetic protein (BMP)-induced signaling and cellular functions. Experimental evidence demonstrated that the mRNA level of BMP5 was significantly higher in ADC tissues compared with that in SCC tissues, and the immunohistochemistry analysis confirmed this result at the protein level (23). However, a correlation between the CTDSPL2 expression level and the occurrence of NSCLC has not been reported to date; it may be a novel biomarker of NSCLC development and progression.…”
Section: Discussionmentioning
confidence: 83%